Liolaemus ramirezae: Headbob display behavior - Vicente, Natalin Soledad (2016)
One of the most common visual signals in lizards is the headbob display. Headbob displays consist of stereotyped up and down movements of the head and/or torso, used in different contexts, such as territorial defense, agonistic interactions, and courtship. Despite the fact that headbob displays are stereotyped and species-specific, their structure reveals variations among sexes, individuals, populations, and social context. The genus Liolaemus, with more than 250 species of neotropical lizardS, offers a great potential to study ecology and evolution of lizard communication. Here we analyze the form and structure of the headbob display of Liolaemus ramirezae lizards, in its natural environment. Liolaemus ramirezae headbob displays were characterized by one long up and down motion (unit 1), followed by a pause and a quick up and down movement of approximately the same amplitude (unit 2). This form was similar among the individuals, possibly corresponding to the signature bob for this species.